A key role for peroxynitrite-mediated inhibition of cardiac ERG (Kv11.1) K(+) channels in carbon monoxide–induced proarrhythmic early afterdepolarizations - Al-Owais, Moza M. (FASEB J, 2017)
Exposure to CO causes early afterdepolarization arrhythmias. Previous studies in rats have indicated that arrhythmias arose as a result of augmentation of the late Na(+) current. The purpose of the present study was to examine the basis for CO-induced arrhythmias in guinea pig myocytes in which action potentials (APs) more closely resemble those of human myocytes. Whole-cell current- and voltage-clamp recordings were made from isolated guinea pig myocytes as well as from human embryonic kidney 293 (HEK293) cells that express wild-type or a C723S mutant form of ether-a-go-go–related gene (ERG; Kv11.1). We also monitored the formation of peroxynitrite (ONOO(−)) in HEK293 cells fluorimetrically. CO—applied as the CO-releasing molecule, CORM-2—prolonged the APs and induced early afterdepolarizations in guinea pig myocytes. In HEK293 cells, CO inhibited wild-type, but not C723S mutant, Kv11.1 K(+) currents. Inhibition was prevented by an antioxidant, mitochondrial inhibitors, or inhibition of NO formation. CO also raised ONOO(−) levels, an effect that was reversed by the ONOO(−) scavenger, FeTPPS [5,10,15,20-tetrakis-(4-sulfonatophenyl)-porphyrinato-iron(III)], which also prevented the CO inhibition of Kv11.1 currents and abolished the effects of CO on Kv11.1 tail currents and APs in guinea pig myocytes. Our data suggest that CO induces arrhythmias in guinea pig cardiac myocytes via the ONOO(−)-mediated inhibition of Kv11.1 K(+) channels.—Al-Owais, M. M., Hettiarachchi, N. T., Kirton, H. M., Hardy, M. E., Boyle, J. P., Scragg, J. L., Steele, D. S., Peers, C. A key role for peroxynitrite-mediated inhibition of cardiac ERG (Kv11.1) K(+) channels in carbon monoxide–induced proarrhythmic early afterdepolarizations.